2002
DOI: 10.1161/hq1201.100456
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Redox State and Endothelial Dysfunction in Mildly Hyperhomocysteinemic Cystathionine β-Synthase–Deficient Mice

Abstract: Abstract-Previous in vitro experiments have shown that hyperhomocysteinemia leads to oxidative inactivation of nitric oxide, in part by inhibiting the expression of cellular glutathione peroxidase (GPx-1). To elucidate the role of intracellular redox status on homocysteine-induced endothelial dysfunction and oxidant stress, heterozygous cystathionine ␤-synthase-deficient (CBS -/ϩ ) and wild-type (CBS ϩ/ϩ ) mice were treated with the cysteine donor L-2-oxothiazolidine-4-carboxylic acid (OTC). CBS -/ϩ mice had s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
120
1
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(128 citation statements)
references
References 63 publications
6
120
1
1
Order By: Relevance
“…2,3 The study is consistent with the demonstrated presence of ADAMTS13 mRNA in endothelial cells 4 and, more importantly, puts the metalloprotease where its substrate ULVWF is synthesized, released, and likely cleaved. Although the data are generated in cell culture, endothelial cells are likely to synthesize the metalloprotease in vivo.…”
Section: Jing-fei Dong Baylor College Of Medicinesupporting
confidence: 80%
See 1 more Smart Citation
“…2,3 The study is consistent with the demonstrated presence of ADAMTS13 mRNA in endothelial cells 4 and, more importantly, puts the metalloprotease where its substrate ULVWF is synthesized, released, and likely cleaved. Although the data are generated in cell culture, endothelial cells are likely to synthesize the metalloprotease in vivo.…”
Section: Jing-fei Dong Baylor College Of Medicinesupporting
confidence: 80%
“…In contrast to the in vitro platelet studies by Dayal and colleagues, Weiss et al 4 showed that mildly hyperhomocysteinemic mice have higher circulating levels of P-selectin, indicating that platelets are activated in vivo by elevated homocysteine. Importantly, Dayal and colleagues found that washed platelets, free from the hyperhomocysteinemic environment, are not altered in their response to thrombin activation.…”
mentioning
confidence: 80%
“…Heterozygous CBSdeficient mice develop endothelial dysfunction by decreasing vascular nitric oxide bioavailability, thereby leading to impaired vasorelaxation. 41,46 This association is not unique to CBS-deficient mice, as endothelial dysfunction has also been observed in other animal models of HHcy, including rabbits and monkeys. 67,[110][111][112][113] Although CBS-deficient mice or non-murine models of HHcy exhibit endothelial dysfunction, there is no evidence of atherosclerotic lesion development.…”
Section: Animal Models Of Hhcy-induced Atherogenesismentioning
confidence: 90%
“…41 It is likely, therefore, that HHcy decreases nitric oxide bioavailability through alternative mechanisms, such as accelerated oxidative inactivation of nitric oxide. 40 Homocysteine-induced oxidative inactivation of nitric oxide has been observed in vitro in cultured endothelial cells, 42 and evidence for increased oxidative inactivation of nitric oxide during HHcy has been obtained in animals using both pharmacological 41,[43][44][45][46] and genetic 47,48 approaches. Several types of reactive oxygen species (ROS), including superoxide, hydrogen peroxide, and peroxynitrite, may contribute to the oxidative inactivation of endothelium-derived nitric oxide in HHcy.…”
Section: Hhcy and Endothelial Cell Dysfunctionmentioning
confidence: 99%
“…These mice, which have elevated level of plasma homocysteine concentrations (Watanabe et al, 1995), also exhibit some pathological features of hyperhomocysteinemia such as endothelial dysfunctions (Eberhardt et al, 2000;Lentz et al, 2000;Dayal et al, 2001;Weiss et al, 2001Weiss et al, , 2002Denis et al, 2003).…”
mentioning
confidence: 99%